Evaluation of Knowledge Management System Using Technology Acceptance Model - Jarot S. Suroso; Astari Retnowardhani (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
This study was motivated to assess the Knowledge Management System (KMS) using Technology Acceptance Model (TAM). TAM is the best concept to be taken as model on explaining user attitude of new technology. TAM model used in the study because it has been widely adopted among IT researchers and appears to be growing rapidly, has the reliability and construct  validity were established, and realized  that the model has not been applied to the acceptance KMS. The data population in this study is the employees in PT. XYZ who have work-related to development and maintenance process. The data analysis  was  done  using  Partial  Least  Squares  (PLS).  The analysis was proof to be statistically significant: a) perceived ease of use and perceived usefulness, b) perceived ease of use and attitude, c) perceived usefulness and attitude, d) perceived usefulness and behavioral intention to use, e) behavioral intention to use and actual use.